Optimalisasi Laporan Keuangan Organisasi Non-Profit Melalui Pelatihan Akuntansi Praktis - Eliana; Sufitrayati; Mawardi (JKA, 2024)
This study aims to explore how practical accounting training can optimize the financial reporting of non-profit organizations. Many non-profit organizations face challenges in preparing accurate and transparent financial reports, which can hinder operational effectiveness and donor trust. The research method used is qualitative with a case study approach on several non-profit organizations in Indonesia. Data were collected through in-depth interviews, observations, and analysis of financial reports before and after practical accounting training. The results show that practical accounting training significantly improves staff understanding and skills in preparing financial reports. Additionally, this training positively impacts the financial transparency and accountability of organizations, thereby increasing donor and stakeholder trust. The study concludes that practical accounting training is an effective tool for optimizing the financial reporting of non-profit organizations and recommends the widespread implementation of similar training programs to enhance the professionalism and sustainability of non-profit organizations.